Assessment of stigmatization in people with epilepsy - G. Pociuvienė; D. Streckytė; R. Mameniškienė (Neurologijos seminarai)
Introduction. Although 50 million people worldwide have epilepsy, the prevalent negative attitudes towards them impair their quality of life and limit opportunities to study and work. To our knowledge, epilepsy stigmatization has not been studied in Lithuania. For this reason, we aimed to assess the attitudes to epilepsy and epilepsy stigmatization in people with epilepsy (PWE). Methods. In October 2019-March 2020, adult PWE completed a newly developed anonymous questionnaire composed of 8 socio-demographic and 20 closed-ended questions to assess epilepsy stigma. Stigmatization was assumed to be non-existing or low at <33 points, average at 33-64 and high at 65-100 points. MS Excel and IBM SPSS 21.0 were used for statistical analysis. Statistical significance was assumed at p<0.05. Results. 129 completed questionnaires were analyzed. Mean age of the subjects was 36±15.8 years; 62% were women. Although 93.8% of PWE have heard/read about epilepsy (p=0.137), 24.8% of them believe that epilepsy is a mental illness (p=0.723); 66.7% think that epilepsy is incurable (p=0.798); 45% reported that society treats PWE differently (more often women, p=0.028), and 63.6% think that PWE face difficulties working and studying (p=0.485). Mean stigma score is 39.3±16.5. The score does not depend on socio-demographic data (p>0.05). A higher score weakly correlates with older age (R=0.2, p=0.024), although higher stigma scores correlate with the opinion that epilepsy is a mental (p=0.026) and incurable illness (p=0.000). Respondents with a higher stigmatization score are more likely to think that PWE face difficulties working or studying (R=0.58, p=0.000) and in relationships (R=0.59, p=0.000) as well as that society has a preconceived negative attitude towards PWE (R=0.46, p=0.000). Stigma level is higher when PWE feel anxiety (R=0.5, p=0.000), shame (R=0.55, p=0.000), fear (R=0.6, p=0.000), sadness (R=0.62, p=0.000) and consider to be depended on other individuals (R=0.68, p=0.000). Conclusions. Lack of knowledge about epilepsy is possibly the main reason for epilepsy stigmatization at the average level: a quarter of respondents with epilepsy believe that epilepsy is a mental illness, more than a fifth believe that epilepsy cannot be controlled and two-thirds believe that it cannot be cured.